2004
DOI: 10.1111/j.1365-2133.2004.05670.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant proliferating trichilemmal tumour and CAV (cisplatin, adriamycin, vindesine) treatment

Abstract: Influence of environmental temperature on the occurrence of non-necrotizing cellulitis of the leg SIR, Non-necrotizing cellulitis of the leg is a common cutaneous bacterial infection whose risk factors include venous insufficiency, lymphoedema and toe-web intertrigo. The role of environmental temperature remains controversial. 1 To study the relationship between environmental temperature and the frequency of non-necrotizing cellulitis of the leg, we reviewed all patients hospitalized with nonnecrotizing cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 7 publications
0
28
0
2
Order By: Relevance
“…There is no established chemotherapy regimen for metastatic TC reported in the medical literature. However, we found that Hayashi et al administered chemotherapy (cisplatin, adriamycin, vindesine: CAV treatment) similar to the regimen used for highly advanced cases of squamous cell carcinoma (9,13).…”
Section: Discussionmentioning
confidence: 70%
“…There is no established chemotherapy regimen for metastatic TC reported in the medical literature. However, we found that Hayashi et al administered chemotherapy (cisplatin, adriamycin, vindesine: CAV treatment) similar to the regimen used for highly advanced cases of squamous cell carcinoma (9,13).…”
Section: Discussionmentioning
confidence: 70%
“…Adjuvant chemotherapy is not thought to be superior to adequate surgery alone 22. The CAV regimen (cisplatin, adriamycin and vindesine) used for advanced SCC has shown only limited benefit 23. In addition, Takenaka et al report a case of MPTT resistant to radiotherapy, chemotherapy (cisplatin, bleomycin, adriamycin) and intralesional ethanol 24.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplazi varlığı, yüksek mitoz oranı ve derin invazyon varlığı agresif karakteristikle ilişkili bulunmuş ve bu grupta nüks oranlarının daha yüksek olduğu bildirilmiştir. Özellikle nüks riskinin yüksek olduğu bu olgularda cerrahiye adjuvan olarak radyoterapi ve/veya kemoterapinin eklenmesi önerilmektedir (10) . Ender olmakla birlikte, lokal nüks ve uzak organ metastazı gelişen olgular da bildirilmiştir (1,3,4,(11)(12)(13)(14)(15) .…”
Section: Discussionunclassified